‏مقالات الشيخ عدون في الصحافة الوطنية - بكوش, محمد بن موسى (جمعية التراث, 2024)
Keywords: Journalisme -- Mzab; Réformisme -- Mzab

“There is no sin in it, unless ...”: Legal reform among the Maghreb Ibāḍīs - Vikør, Knut S. (Between Morocco and Indonesia and beyond: Essays in honour of Irene Schneider, 2024)
Keywords: Réformisme -- Mzab

Al-Umma Al-Yaqzaniyya’s Self-Representation: A Key to Understanding Algerian Reformism - Emara, Nagat (Middle East Studies Association 58th Annual Meeting, 2024)
Keywords: Journalisme -- Mzab; Réformisme -- Mzab

Society and Religion in 20th Century Algeria : Ibadite Reform, Between Modernization and Conservation - Salhi, Mohamed Brahim (Insaniyat / إنسانيات. Revue algérienne d'anthropologie et de sciences sociales, 2024)
Ibadite religious reform in the M’zab, is precocious and internal. It starts from the established fact that the Ibadite rite in its initial version doesn’t correspond to the demands imposed by XXth C changes. In this sense it is closer to, the renaissance (Nahda) which germed in the orient at the end of the 19th C early 20th C. It shares many principles with the Badissian reform to which it is allied.However, the Ibadite community’s particularity, imposes the respect of community preservation on its reformers .It also finds there a powerful factor for legalizing to captivate innovations for economic and material modernization. The advancement of the religious reform doesn’t happen without offending conservators of the rite in its purity and its references judged as untouchable.This contribution intends to draw a picture which shows how little by little this reform is outlined, takes shape then takes root, opening an alternative, adapting to change, which is captivated and used as a conservation tool by this particular community.
Keywords: Réformisme -- Mzab

The rise of an Ibadi religious revival movement and its impacts on the society and built environment in the Mzab (Saharan Maghrib, 1868-1914) - Kwan, Elisabeth (University of Cambridge, 2024)
This study is about the rise of a nineteenth century religious renewal movement among Ibadi Mzabis, a sectarian and Saharan community. It looks at how this group responded to the local effects of a re-globalising world and redefined its sectarian identity to strengthen itself. The movement, which I call the Ibadi Mzabi *nahḍa*, began in the late 1860s when the community was faced with multiple pressures leading to social division. A cosmopolitan network of merchant-scholars drew on ideas which were circulating among broader Arab-Muslim cultural, intellectual and other religious *nahḍa* movements at the time. Some of these ideas shaped the way in which this local movement was expressed in its textual and built works. During a period of pressure in the 1870s and 1880s, there was a rise in the production of new texts. Through these new texts, there was a renewal of Ibadi religious law and rise in the authority of Ibadi religious scholars, and an increasing recognition that Mzabis were Ibadis rather than Kharijis. In Ghardāya, this rise in sectarianism resulted in the suppression of religious diversity in the public sphere and encouraged the integration of Muslims of multiple identities into a common and "renewed" Ibadi Mzabi community. During a period of prosperity and stability in the late 1890s, new commemorative shrines were built as part of this Ibadi Mzabi *nahḍa*. Through these shrines, new ideas of sectarian identity were expressed in the landscape, substantiating the historical legacy of contemporary Ibadi scholars and expressions of Ibadism in the Mzab.
Keywords: Réformisme -- Mzab

المشروع الإصلاحي في وادي ميزاب، الإنجازات والتحديات - الشيخ بالحاج, قاسم بن أحمد (الملتقى العِلمي حول فكر وجهود الفقيه المصلح الشيخ محمَّد بن بكير رشوم رحمه الله (1964-2011), 2024)
Keywords: Réformisme -- Mzab

الشيخ محمد ارشوم ومنهجه في الإصلاح الاجتماعي - بعوشي, عبد الله بن باعلي (الملتقى العِلمي حول فكر وجهود الفقيه المصلح الشيخ محمَّد بن بكير رشوم رحمه الله (1964-2011), 2024)
Keywords: Réformisme -- Mzab

A l'ombre de la nation, les continuités inattendues de l'historiographie mozabite dans les années 1960-1970 - Jomier, Augustin (Les étudiants et la décolonisation aux années 1960 au Maghreb, 2024)
Keywords: Réformisme -- Mzab

الشيخ بيوض كاتبا صحفيا - بكوش, محمد بن موسى (الأيام الثقافية لختمة تفسير القرآن الكريم, 2024)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Journalisme -- Mzab; Réformisme -- Mzab